A Hospital's Legal Responsibility For Patient Rights During The COVID-19 Pandemic - A Review From The Health Sector's Law Regulations - Yohanes Firmansyah,; St. Laksanto Utomo, (Jurnal Indonesia Sosial Sains, 2021)
The hospital's legal responsibility to fulfill the patient's rights cannot be separated from the hospital's obligations to the patient, according to the law. In practice, the growing number of COVID-19 cases in Indonesia has resulted in hospitals being unable to accommodate patients in need of treatment, particularly those with severe and critical conditions who require intensive care units. With bed occupancy rates (BOR) exceeding 85 percent in almost all hospitals, the community must understand that hospitals must prioritize care for patients with moderate, severe, or life-threatening conditions. In any case, the COVID-19 pandemic had an effect on the quality of hospital care provided to patients. The study used normative juridical research methods and empirical evidence to examine hospitals' legal responsibility for upholding patient rights during the COVID-19 pandemic. The study's findings indicate that, despite limitations in providing excellent health care to patients, hospitals must uphold patient rights to safety and security during hospitalization. As a result, it is necessary to establish a legal framework that protects the rights of health care workers and hospitals providing services to patients during this pandemic, particularly the protection of work standards, occupational health and safety standards, and labor social security standards. In terms of facilities and infrastructure, the government must assist by increasing the number of emergency hospitals to accommodate the anticipated increase in COVID-19 patients.